2002
DOI: 10.1038/sj.cdd.4401065
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-6 is the direct activator of caspase-8 in the cytochrome c-induced apoptosis pathway: absolute requirement for removal of caspase-6 prodomain

Abstract: Caspase activation resulting from cytochrome c release from the mitochondria is an essential component of the mechanism of apoptosis initiated by a range of factors. The activation of Bid by caspase-8 in this pathway promotes further cytochrome c release, thereby completing a positive feedback loop of caspase activation. Although the identity of the caspases necessary for caspase-8 activation in this pathway are known, it is still unclear which protease directly cleaves caspase-8. In order to identify the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
172
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(185 citation statements)
references
References 32 publications
(32 reference statements)
9
172
0
1
Order By: Relevance
“…In contrast, the role of caspase-8 was far less discriminating between the two pathways; both extrinsic and intrinsic apoptotic events were inhibited by caspase-8 inhibitors, and both were accompanied by cleavage of caspase-8. These observations either indicate a previously undescribed attribute of caspase-8 as a mediator of intrinsic apoptosis, as suggested in some studies (38)(39)(40), or reflect an endogenous extrinsic apoptotic pathway in CD10 ϩ B cells that was mediated by an unidentified death receptor and its membrane-bound ligand. However, considering that we have found no evidence for the latter possibility (our unpublished data), yet clear evidence for differences between untreated CD10 ϩ and CD95L-treated CD10 Ϫ B cells regarding response to caspase-8 inhibition and kinetics of caspase-8 cleavage, we believe the data are more consistent with an intrinsic apoptotic pathway in CD10 ϩ B cells involving a unique form of caspase-8 activation.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, the role of caspase-8 was far less discriminating between the two pathways; both extrinsic and intrinsic apoptotic events were inhibited by caspase-8 inhibitors, and both were accompanied by cleavage of caspase-8. These observations either indicate a previously undescribed attribute of caspase-8 as a mediator of intrinsic apoptosis, as suggested in some studies (38)(39)(40), or reflect an endogenous extrinsic apoptotic pathway in CD10 ϩ B cells that was mediated by an unidentified death receptor and its membrane-bound ligand. However, considering that we have found no evidence for the latter possibility (our unpublished data), yet clear evidence for differences between untreated CD10 ϩ and CD95L-treated CD10 Ϫ B cells regarding response to caspase-8 inhibition and kinetics of caspase-8 cleavage, we believe the data are more consistent with an intrinsic apoptotic pathway in CD10 ϩ B cells involving a unique form of caspase-8 activation.…”
Section: Discussionmentioning
confidence: 56%
“…Here, we present strong evidence for the latter, as SFV-induced caspase-8 and Bid processing was inhibited in BakÀ/À and Bax/Bak DKO MEFs. As previously suggested, 29,30 this downstream pathway may be necessary to further activate Bak (and Bax) by tBid, ensuring effective release of apoptogenic factors from mitochondria and the execution of both caspase-dependent and caspase-independent forms of cell death. For SFVinduced apoptosis, this indeed seems to be important as both BidÀ/À and Bid/Bim DKO MEFs died in a significantly delayed manner.…”
Section: Discussionmentioning
confidence: 77%
“…23,24 However, as the caspase-8/tBid pathway can also be activated downstream of mitochondria, presumably via caspase-6-and/or caspase-3-mediated processing of caspase-8 and/or Bid, 29 it has remained unclear if the reported apoptosis-inhibitory effects of crmA and vFLIP were due to death receptor signalling or due to the downstream mitochondrial pathway. Here, we present strong evidence for the latter, as SFV-induced caspase-8 and Bid processing was inhibited in BakÀ/À and Bax/Bak DKO MEFs.…”
Section: Discussionmentioning
confidence: 99%
“…43 Interestingly, although plants do not have homologs of animal lamins, 44 and programmed cell death in spruce embryos does not involve strong chromatin condensation, 23 we observed decreased frequency of DNA fragmentation in zVAD-fmkand zVEID-fmk-treated cultures (Figure 5a). Apart from the role of caspase-6 as one of the downstream caspases, a recent study of Cowling and Downward 45 revealed an additional, upstream role of caspase-6 in direct activation of initiator procaspase-8 in Fas-triggered apoptosis.…”
Section: Discussionmentioning
confidence: 99%